The Influence of System Quality and Perception of Ease of Use on The Success of Using E-Procurement Systems in the Open University - Susilo Edi Prianto; Antonius Setyadi (Dinasti Publisher, 2023)
The purpose of this study was to determine the effect of system quality and perceived ease of use on the successful use of the e-procurement system at the Open University. Design/methodology/approach - The population in this study were 357 internal users of the e-procurement system at the Open University, a sample of 107 people was determined proportionally to the conditions of the population strata. The analytical method used in this study is descriptive statistics and multiple linear regression analysis with SPSS 22 software. Findings – The results showed that system quality had a positive and significant effect on the successful use of the e-procurement system and perceived ease of use had a positive and significant effect on the successful use of the e-procurement system. While the results of simultaneous measurements, system quality and perceived ease of use also have a positive and significant effect on the successful use of the e-procurement system at the Open University.